Sympathetic nervous system activity in stress and biofeedback relaxation. - Shusterman, V. (IEEE Engineering in medicine and biology magazine)
This article describes several studies on the measurement of slow rhythms in the heart and in peripheral vasculature and their relationship to stress and relaxation. These studies are preliminary steps in an attempt to quantify stress and relaxation. Mental stress is a major, well-documented factor in the development of cardiovascular diseases; relaxation, however, is perceived as the opposite state, which, presumably, can negate these harmful effects. To compare the effects of stress-management or relaxation techniques, stress and relaxation must be first quantified. Three methods for quantifying sympathetic activity as an indicator of stress were analyzed. These are heart-rate variability (HRV), photoplethysmographic measurement of peripheral vasomotor activity, and a novel measurement of skin temperature variability. The study showed that due to "low pass filtering response" of the thermal-transfer function between the blood vessel and the skin's temperature, the temperature-variability measurement is minimally sensitive to mechanical factors or accidental noise. Therefore, the temperature variability could be useful for the continuous tracking of vascular activity and its sympathetic tone. Tracking changes in the pressure-wave envelope (PV) provides another alternative for studying sympathetic nervous system (SNS) effects on peripheral vasculature. A drastic reduction in PV and a loss of correlation between temperature variability on the left and right hand confirm the predominant role of SNS in mediating these signals. Functional responses of these signals to SNS-stimulating (mental stress) or blocking (biofeedback) maneuvers are perturbed in patients with CAD (coronary artery disease), suggesting that these tests could be used as simple diagnostic or screening tools.